Prophylactic use of an anti-activated factor XII monoclonal antibody, garadacimab, for patients with C1-esterase inhibitor-deficient hereditary angioedema: a randomised, double-blind, placebo-controlled, phase 2 trial. Issue 10328 (5th March 2022) - Craig, Timothy; Magerl, Markus; Levy, Donald S; Reshef, Avner; Lumry, William R; Martinez-Saguer, Inmaculada; Jacobs, Joshua S; Yang, William H; Ritchie, Bruce; Aygören-Pürsün, Emel; Keith, Paul K; Busse, Paula; et al.
Summary: Background: Hereditary angioedema is associated with dysregulation of the kallikrein–kinin system. Factor XII (FXII) is a key initiator of the kallikrein–kinin system, which produces bradykinin, a central mediator of angioedema. Garadacimab (CSL Behring) is a first-in-class, fully human, immunoglobulin G4 monoclonal antibody targeting activated FXII, intended to prevent attacks in patients with C1-esterase inhibitor-deficient hereditary angioedema (HAE-C1-INH). We aimed to investigate garadacimab as a treatment every 4 weeks for patients with HAE-C1-INH. Methods: In this double-blind, placebo-controlled, phase 2 study, patients with HAE-C1-INH were recruited from 12 research centres in Canada, Germany, Israel, and the USA. Eligible patients were aged 18–65 years and must have had at least four attacks of any severity over a consecutive 2-month period during the 3 months before screening or initiation of previous hereditary angioedema prophylaxis. After a run-in period of 4–8 weeks, patients were randomly assigned (1:1:1:1), using an interactive response technology via block randomisation (block sizes of 1–4), to either placebo or 75 mg, 200 mg, or 600 mg garadacimab. Patients were given an initial intravenous loading dose, and then, on day 6 and every 4 weeks for 12 weeks, they were given a subcutaneous dose of their allocated treatment. The primary endpoint was the number of monthly attacks in the intention-to-treat population (defined as all patients who underwent screening, provided consent, and were assigned to treatment) during the 12-week subcutaneous administration period assessed in the 200 mg and 600 mg garadacimab groups versus placebo. Safety was assessed in all patients who received at least one dose or partial dose of study treatment. This study is registered with ClinicalTrials.gov, NCT03712228 . Findings: Between Oct 29, 2018, and Aug 28, 2019, 54 patients were screened, of whom 32 were randomly assigned to either placebo (n=8) or 75 mg (n=9), 200 mg (n=8), or 600 mg (n=7) garadacimab. The median age was 39·5 years (28·0–52·5) and 18 (56%) of 32 patients were female and 14 (34%) were male. The median number of monthly attacks during the 12-week subcutaneous treatment period was 4·6 (IQR 3·1–5·0) with placebo, 0·0 (0·0–0·4) with 75 mg garadacimab, 0·0 (0·0–0·0) with 200 mg garadacimab, and 0·3 (0·0–0·7) with 600 mg garadacimab. Compared with placebo, the rate of attacks was significantly reduced with garadacimab at 200 mg (reduced by 100% [95% CI 98–101]; p=0·0002) and 600 mg (reduced by 93% [54–110]; p=0·0003). No serious adverse events, deaths, or adverse events of special interest (anaphylaxis, thromboembolic events, and bleeding events) were observed. Interpretation: Garadacimab 200 mg and 600 mg every 4 weeks significantly reduced the number of monthly attacks versus placebo and was well tolerated during the study. Garadacimab is an efficacious, subcutaneous prophylaxis in patients with HAE-C1-INH and warrants phase 3 evaluation. Funding: CSL Behring.